EFFECT OF BRAND IMAGE, GREEN MARKETING STRATEGY , AND EMOTIONAL DESIRE FOR PURCHASING DECISIONS IN PRODUCTS STARBUCKS JAKARTA - Henry Meytra Taufik; Gio Hadi Utama (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2022)
Influence brands image, green marketing strategy, and emotional desires to decision purchase Starbucks product . Study this aim for knowing influence brand image , green marketing strategy , and emotional desire for decision purchase Starbucks products in Jakarta. Data obtained through deployment questionnaire in link form and distributed through social media to ever respondent _ consume Starbucks products and that's back and worth it is as many as 111 respondents came from from five cities in Indonesia , namely Denpasar, Jakarta, Bandung, Surabaya and Medan. The analytical technique used in study this that is technique analysis multiple linear regression with SPSS. Test results in study this obtained mark coefficient regression brand image (X 1 ) and emotional desire (X 3 ) variables of 0.318 and 1.298, with mark significance both of them of 0.000 , brand image and emotional desire have influence positive and significant to decision purchase Starbucks product . Coefficient value regression variable green marketing strategy (X 2 ) of 0.100 with mark significance of 0.136 so that green influential marketing strategy positive however no significant to decision purchase product Starbucks. As for the results from coefficient determination of 0.770 which means 77% can explain models or the influence of each variable to decision purchases , meanwhile the remaining 23% explained by reasons other outside model study this .